Strategies for the Creation and Maintenance of Reconstructed Arteriovenous Fistulas Using the Forearm Basilic Vein. Issue 5 (28th February 2013) - Kumano, Shintaro; Itatani, Keiichi; Shiota, Jun; Gojo, Satoshi; Izumi, Naoki; Kasahara, Hitoshi; Homma, Yukio; Tagawa, Hitoshi
Abstract Reconstruction of an arteriovenous fistula (AVF) after an initial failure to provide long‐term patency has been desired in the era when hemodialysis patients' prognosis is improving. The forearm basilic vein AVF should be considered, before an artificial graft shunt or an AVF in the cubital region. The present study was designed to establish a strategy for the creation and maintenance of AVFs using the forearm basilic vein. This study reviewed 76 cases of reconstructed AVF including 18 cases using the basilic vein (23.7% of total cases). The following four points were considered: arm positioning of the cubital flexion position combined with the forearm supinated position; several small skin incisions with a subcutaneous tunnel; sufficient venous dilatation using Fogarty balloon catheter; and early percutaneous angioplasty introduction for immature AVF. The primary and secondary patency rates were examined. A radiobasilic AVF was created through a subcutaneous tunnel in two cases. The primary and secondary patency rates of AVF with the basilic vein were 54.7% and 76.7% respectively, whereas those of AVF with the cephalic vein were 49.3% and 71.3%. The basilic was not inferior to the cephalic vein (P‐value of the log‐rank test for primary and secondary patency rates were 0.927 and 0.811, respectively). Early stage percutaneous angioplasty was effective in five cases with immature AVF. The forearm basilic vein was useful in AVF reconstruction and equivalent to radiocephalic reconstruction. Careful observation and percutaneous angioplasty during the early period after the surgery were essential for long‐term patency.